Optimalisasi Hasil Produksi Briket Cangkang Kelapa Dengan Memanfaatkan Teknologi Tepat Guna Berbahan Bakar Minyak Solar - Teuku Zulfadli; Muhammad Kafrawi; Misswar Abd (Infotekmesin, 2022)
Many methods can be used by the community to burn coconut shells into charcoal, one of which is by utilizing appropriate technology fueled by diesel oil, namely shell powder processing machines. The production of briquettes from coconut shells is still limited and has not developed rapidly because the process of shelling coconut shells is still simple thus it takes three to five days. The use of adhesive amounts is not optimal. This is done to fulfill the community's desire; therefore, coconut shell waste can be managed as raw material for making briquettes to become a source of community income. The purpose of this research is to optimize the production of coconut shell briquettes by utilizing appropriate technology fueled by diesel oil. The method used is by conducting a trial process of starch adhesive treatment, namely 1%, 2%, 3%, 4%, 5%, 6%, 6.25%, and 7% with the amount of water 900 ml at a temperature of 70 0C to form gelatinization. As a result, it was found that the best starch adhesive treatment is in the 6.25% test with the ratio of the starch adhesive mixture, shell powder, and water being 0.25: 4: 0.9. It indicates that the resulting briquette shape is more efficient, has high density and small briquette pores.